Prevalence and Clinicopathological Features with Oral Biological Correlates of Potentially Malignant Oral Disorders in Individuals with High-Risk Oral Habits - Jalil, Varda; Rahman, Maida; Nazir Kiani, Maryam; Tehseen, Jawahir; Akram, Zain; Waqas Rashid, Muhammad (Journal of Neonatal Surgery, 2025)
Objective: To determine the prevalence, clinicopathological characteristics, and oral biological correlates of potentially malignant oral disorders (PMODs) in individuals with high-risk oral habits. Materials and Methods: It was an analytical cross-sectional study carried out in a period of one year. Non-probability consecutive sampling was used to enroll 150 participants aged ≥18 years with high-risk oral habits. The oral cavity clinical examination was conducted, and a biopsy of suspected lesions was done to examine them histopathologically. SPSS version 24 was used to analyze the data. The descriptive statistics were provided in frequencies, percentages, and mean ± SD. The Chi-square test was used to assess the associations, and p ≤ 0.05 was regarded as significant. Results: The average age of the subjects was 39.8 ± 12.4 years, and the male gender prevailed (68%). Smokeless tobacco use (34.7%) was the most common high-risk habit. PMODs were found in a quarter of the participants. The expression of Ki-67 (69.4%) was more than that of p53 (58.3), and the expression of biomarkers rose greatly as the severity of dysplasia increased (p = 0.001). There was a considerable correlation between high-risk oral habits and PMODs (p = 0.032). Conclusions: PMODs are common in patients with high-risk oral habits, and the severity of PMODs is associated with biomarker expression. To avoid malignant transformation, early detection, quitting a habit, and a combination of clinical, pathological, and biological evaluation is needed.